Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ijscr.2018.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal ectopic thyroid mass with normal thyroid function and location: Case report

Abstract: HighlightsEctopic Thyroid Tissue in the mediastinum is very rare.ETT can be associated with normal thyroid function and normal thyroid anatomical location.ETT should be differentiated from substernal goiter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…As for the presence of orthotopic thyroid glands, no eutopic thyroids were observed in 70%-75% of lingual thyroids, and in addition, most of the lingual thyroid cases were hypothyroidism [5,11,12]. In reports of mediastinal ectopic thyroids, they seemed to have orthotopic thyroid and euthyroid function in most of the cases [5,7,8,[13][14][15][16][17][18]. However, Santangelo et al reported five cases of ectopic thyroids in the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the presence of orthotopic thyroid glands, no eutopic thyroids were observed in 70%-75% of lingual thyroids, and in addition, most of the lingual thyroid cases were hypothyroidism [5,11,12]. In reports of mediastinal ectopic thyroids, they seemed to have orthotopic thyroid and euthyroid function in most of the cases [5,7,8,[13][14][15][16][17][18]. However, Santangelo et al reported five cases of ectopic thyroids in the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the ectopic thyroid in the mediastinum was not connected with the orthotopic thyroid gland, and the blood flow was supplied from the thorax sides, which was demonstrated both on the CT image and in intraoperative findings. It has been reported that sternotomy or thoracotomy is essential for the removal of a mediastinal ectopic goiter, which receives blood flow from the thorax; therefore, in most of the cases, surgical resection was performed through sternotomy or thoracotomy [ 3 , 4 , 6 , 12 , 14 - 17 , 19 ]. However, there have been some reports of mediastinum ectopic thyroids resected only through a cervical incision, but in all cases, concomitant resection of the orthotopic thyroids was performed [ 7 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common location of ectopic thyroid tissue is base of tongue (lingual thyroid) in about 90% of cases, as reported in the literature. [12] The presence of ectopic thyroid tissue in the mediastinum due to overt descent along thyroglossal duct is a rare entity accounting for approximately 1% of all ectopic locations of the thyroid. [1] It usually occurs along with normally functioning thyroid gland in the neck.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The presence of ectopic thyroid tissue in the mediastinum due to overt descent along thyroglossal duct is a rare entity accounting for approximately 1% of all ectopic locations of the thyroid. [1] It usually occurs along with normally functioning thyroid gland in the neck. [2] Coexisting Graves’ disease is a further rare entity with only five cases reported till now.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 Radiological imaging studies such as ultrasound, CT scan and magnetic resonance imaging may be helpful in knowing the extension of thyroid, but the best diagnostic test for isolated mediatinal thyroid is thyroid scanning with technetium-99 m. Tissue biopsy can be performed using many methods such as CT-guided fine needle aspiration, EBUS-transbronchial needle aspiration or surgical excision. 5 Surgical resection is the gold standard treatment. Its role is both diagnostic and therapeutic, it allows diagnosis by providing tissue for histological study, it also allows to rule out malignancy and to remove compression of adjacent structures, such as trachea and heart to prevent the risk of tracheomalacia, heart rhythm disorders.…”
Section: Discussionmentioning
confidence: 99%